Novel pathologic scoring tools predict end-stage kidney disease in light chain (AL) amyloidosis. (3rd July 2017) - Rubinstein, Samuel; Cornell, Robert F.; Du, Liping; Concepcion, Beatrice; Goodman, Stacey; Harrell, Shelton; Horst, Sara; Lenihan, Daniel; Slosky, David; Fogo, Agnes; Langone, Anthony
Abstract: Background and objectives: Light chain (AL) amyloidosis frequently involves the kidney, causing significant morbidity and mortality. A pathologic scoring system with prognostic utility has not been developed. We hypothesized that the extent of amyloid deposition and degree of scarring injury on kidney biopsy, could provide prognostic value, and aimed to develop pathologic scoring tools based on these features. Methods: This is a case-control study of 39 patients treated for AL amyloidosis with biopsy-proven kidney involvement at a large academic medical center. Our novel scoring tools, composite scarring injury score (CSIS) and amyloid score (AS) were applied to each kidney biopsy. The primary outcome was progression to dialysis-dependent end-stage kidney disease (ESKD) using a 12-month landmark analysis. Results: At 12 months, nine patients had progressed to ESKD. Patients with an AS ≥7.5 had a significantly higher cumulative incidence of ESKD than those with AS <7.5 ( p  = .04, 95% CI 0.13–0.64). Conclusions: Using a 12-month landmark analysis, AS correlated with progression to ESKD. These data suggest that a kidney biopsy, in addition to providing diagnostic information, can be the basis for a pathologic scoring system with prognostic significance.